MyD88 and STING Signaling Pathways Are Required for IRF3-Mediated IFN-β Induction in Response to Brucella abortus Infection - de Almeida, Leonardo A.; Carvalho, Natalia B.; Oliveira, Fernanda S.; Lacerda, Thais L. S.; Vasconcelos, Anilton C.; Nogueira, Lucas; Bafica, Andre; Silva, Aristóbolo M.; Oliveira, Sergio C. (PloS one, 2011)
Type I interferons (IFNs) are cytokines that orchestrate diverse immune responses to viral and bacterial infections. Although typically considered to be most important molecules in response to viruses, type I IFNs are also induced by most, if not all, bacterial pathogens. In this study, we addressed the role of type I IFN signaling during Brucella abortus infection, a facultative intracellular bacterial pathogen that causes abortion in domestic animals and undulant fever in humans. Herein, we have shown that B. abortus induced IFN-β in macrophages and splenocytes. Further, IFN-β induction by Brucella was mediated by IRF3 signaling pathway and activates IFN-stimulated genes via STAT1 phosphorylation. In addition, IFN-β expression induced by Brucella is independent of TLRs and TRIF signaling but MyD88-dependent, a pathway not yet described for Gram-negative bacteria. Furthermore, we have identified Brucella DNA as the major bacterial component to induce IFN-β and our study revealed that this molecule operates through a mechanism dependent on RNA polymerase III to be sensed probably by an unknown receptor via the adaptor molecule STING. Finally, we have demonstrated that IFN-αβR KO mice are more resistant to infection suggesting that type I IFN signaling is detrimental to host control of Brucella. This resistance phenotype is accompanied by increased IFN-γ and NO production by IFN-αβR KO spleen cells and reduced apoptosis.